Pressure Ulcers in Older Adults: A Prevalence Study. (October 2015) - Rasero, Laura; Simonetti, Monica; Falciani, Francesca; Fabbri, Cristina; Collini, Francesca; Dal Molin, Alberto
ABSTRACT: OBJECTIVE: The purpose of this study was to measure the prevalence of pressure ulcers (PrUs) in an older adult population. DESIGN: A cross-sectional study. SETTING: The study included all the individuals being cared for in the units of medicine, surgery, intensive care, and medical-surgical specialties of 47 hospitals, 57 public nursing homes, and 37 home care services. PARTICIPANTS: The authors' observational study included 11, 957 patients older than 70 years. MAIN OUTCOME MEASURES: Of the population, 50.75% (6067) were assessed to be at risk of developing PrUs according to the Braden Scale, and 24.66% (2949) had already developed PrUs. In addition, a significant association was found between increased risk (Braden <16) and the presence of PrUs with an odds ratio (OR) of 8.71 (confidence interval [CI], 7.52–10.10) in high-risk subjects (Braden ⩽12) and an OR of 3.86 (CI, 3.36–4.44) in very high-risk patients (Braden 13–16). In the survey, 84.6% of the subjects with PrUs were incontinent, and incontinence increased the risk of developing PrUs in the authors' sample (OR, 1.54; CI, 1.34–1.77). CONCLUSIONS: The authors' data reported in the literature show that the prevalence of PrUs increases as an individual ages. The authors gathered data that showed a large area of intervention in managing the prevention of PrUs, such as an adequate use of protective aids, correcting malnutrition, and controlling incontinence. These results suggest that clinicians should focus more on the prevention of PrUs in older adults.